The mycotoxin alternariol induces DNA damage and modify macrophage phenotype and inflammatory responses. Issue 1 (19th November 2015) - Solhaug, A.; Wisbech, C.; Christoffersen, T.E.; Hult, L.O.; Lea, T.; Eriksen, G.S.; Holme, J.A.
Highlights AOH modifies morphology and cytokine-profile of RAW 264.7 and primary macrophages. Changes endocytosis, autophagy and surface receptors differently in the two models. Induced double strand DNA breaks was associated with the morphological changes.